Neutralization of Interleukin-10 Significantly Enhances Gamma Interferon Expression in Peripheral Blood by Stimulation with Johnin Purified Protein Derivative and by Infection with Mycobacterium avium subsp. paratuberculosis in Experimentally Infected Cattle with Paratuberculosis - Buza, Joram J. (American Society for Microbiology, 2004)
Monoclonal antibody neutralization of interleukin-10 (IL-10) increased Johnin purified protein derivative-induced whole-blood gamma interferon (IFN-γ) secretion 23-fold and also increased IFN-γ secretion ninefold following in vitro Mycobacterium avium subsp. paratuberculosis infection of peripheral blood mononuclear cells. These results demonstrate the suppressive effect of IL-10 on immune responses to M. avium subsp. paratuberculosis infection in cattle.